Repetitive transcranial magnetic stimulation across neurodegenerative diseases: a systematic review and dose-response meta-analysis - Zhang, Yu; Wang, Yulin; Xu, Ke; Zhang, Chengguang; Lv, Peizhu; Bai, Yan; Wang, Shun (Frontiers in Aging Neuroscience, 2025)
ObjectiveWe summarized the existing clinical evidence of repetitive transcranial magnetic stimulation (rTMS) for Parkinson’s Disease (PD) and Alzheimer’s Disease (AD) and conducted a series of dose-response meta-analyses to determine the curve relationship between the number of pulses and the effect size of the treatment.MethodsExisting evidence was retrieved from five databases, and relevant outcome data on rTMS treatment for motor and non-motor symptoms of PD and AD were collected. Data were analyzed using R software to assess effect size using standardized mean differences (SMD) and 95% confidence intervals (CI). Heterogeneity testing was performed to assess differences in efficacy among the evidence, and restricted cubic spline (RCS) was used to fit the dose-response curves.ResultsA total of 51 publications were included, involving 1,938 subjects. We found that for PD patients, the total number of rTMS pulses showed significant bell-shaped curves in TUG (χ2 = 6.87, df = 2, p = 0.03), FOGQ (χ2 = 15.17, df = 2, p = 0.001), BDI (χ2 = 14.33, df = 2, p = 0.001), HAMD (χ2 = 12.63, df = 2, p = 0.001), and HAMA (χ2 = 6.06, df = 2, p = 0.04). For AD patients, the total number of rTMS pulses demonstrated significant bell-shaped curves for MMSE (χ2 = 8.76, df = 2, p = 0.01) and MoCA (χ2 = 6.79, df = 2, p = 0.03).ConclusionOur dose-response meta-analysis results show that rTMS demonstrates significant efficacy in certain motor and non-motor symptoms of PD and AD. The number of rTMS pulses presents a typical bell-shaped curve for these symptoms, indicating that more number of rTMS pulses is not always better; beyond a certain threshold, increasing the number of rTMS pulses correlates negatively with therapeutic efficacy.